2011
DOI: 10.1080/03069885.2010.531384
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a school counselling service with direct links to Child and Adolescent Mental Health (CAMH) services

Abstract: An evaluation of a Scottish secondary school based counselling service for students aged 11 to 18 is presented. Improvement in student emotional well-being was measured using the Young Persons Clinical Outcomes for Routine Evaluation (YP CORE) questionnaire and participant questionnaires which were developed for the study. Significant improvements were found, following counselling, for functioning, problems and well-being, with all three showing a large effect size. The counselling service was rated as helpful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
7
13
0
1
Order By: Relevance
“…The outcomes of interagency collaborative initiatives were generally reported to be positive (Morrissey et al 1997;Loutzenhiser & Hadjistavropoulos 2008;Rowlandson & Smith 2009;McKenzie et al 2011;Vostanis et al 2012;Aupont et al 2013;Hamilton et al 2014). This included reduced time from referral to diagnosis and intervention (Rowlandson & Smith 2009), increased ratings of adequacy and availability of services (Morrissey et al 1997), and increased ratings of partnership between professionals (Hamilton et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of interagency collaborative initiatives were generally reported to be positive (Morrissey et al 1997;Loutzenhiser & Hadjistavropoulos 2008;Rowlandson & Smith 2009;McKenzie et al 2011;Vostanis et al 2012;Aupont et al 2013;Hamilton et al 2014). This included reduced time from referral to diagnosis and intervention (Rowlandson & Smith 2009), increased ratings of adequacy and availability of services (Morrissey et al 1997), and increased ratings of partnership between professionals (Hamilton et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This included reduced time from referral to diagnosis and intervention (Rowlandson & Smith 2009), increased ratings of adequacy and availability of services (Morrissey et al 1997), and increased ratings of partnership between professionals (Hamilton et al 2014). In addition, in four of these studies, the initiatives were rated positively by professionals (Rowlandson & Smith 2009;McKenzie et al 2011;Vostanis et al 2012;Hamilton et al 2014), and two studies showed acceptable outcomes and utilization rates (McKenzie et al 2011;Aupont et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Information about the kind of issues that young people present with to school‐based counselling – that is, are referred for or raise on initial assessment – has been provided by counsellors' records, indicating that the most prevalent topic is family issues (approximately one‐third of all young people) (Cooper, 2009; Hill et al, 2011; McKenzie, Murray, Prior, & Stark, 2010). Anger is the second most common presenting issue (approximately 16% of all young people), and is significantly more common for males (26.08%) than females (8.73%) (Cooper, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been a number of studies looking at school counselling. These have included reviews and audits of studies (Cooper, , ), evaluation of school counselling services (Hill et al., ; Mckenzie, Murray, Prior & Stark, ), evaluation of counselling efficacy (Cooper, ; Fox & Butler, ; Lynass, Pykhtina & Cooper, ; McArthur, Cooper & Berdondini, ; Murdoch et al., ; Rupani, Haughey & Cooper, ) and attitudes of other professionals and counsellors working with other professionals (Cromarty & Richards, ; Hamilton‐Roberts, ; Pybis, Hill, Cooper & Cromarty, ; Spong, Waters, Dowd & Jackson, ).…”
Section: Introductionmentioning
confidence: 99%